Neuroprotective role of dexpanthenol and butafosfan-vitamin b12 against brain damage induced by circadian rhythm disorder - Simge GARLI; Özlem ÖZMEN; Şerife TAŞAN (Kafkas Universitesi Veteriner Fakültesi Dergisi)
This study investigates the neuroprotective effects of dexpanthenol (DEX) and butafosfan-vitmain B12 combination (BUT) in a circadian rhythm disorder (CRD)- induced brain damage model in mice. Control, CRD, DEX, BUT, and BUT + DEX groups were subjected to a 19-day experimental period during which CRD was induced by repeated phase shifts in the light/dark cycle. The CRD group experienced circadian rhythm disorder, while the DEX and BUT groups received intraperitoneal DEX (1000 mg/kg/day) and subcutaneous BUT (200 mg/kg/day) treatments, respectively, for the same duration. Serum cortisol and creatine kinase (CK) levels were measured using ELISA to assess stress and tissue damage. Brain tissues were evaluated histopathologically using hematoxylin and eosin staining, and immunohistochemically for brain-derived neurotrophic factor (BDNF) and glial fibrillary acidic protein (GFAP) expression using specific monoclonal antibodies. CRD significantly increased serum cortisol and CK levels compared to the control group (P<0.001). Both DEX and BUT treatments reduced these elevations, with the combination therapy showing the most pronounced effect (P<0.001). Histopathological examination revealed reduced neuronal degeneration, hyperemia, and hemorrhage in the treatment groups compared to the CRD group. Immunohistochemical analysis showed significantly increased BDNF and GFAP expression in the BUT + DEX group (P<0.001). These findings suggest that DEX and BUT, particularly in combination, exert neuroprotective effects against CRD-induced brain injury by modulating oxidative stress, inflammation, and neurotrophic signaling pathways.